The effectiveness of promotional strategy implemented by Zoo Melaka / Nur Syahidah Ahamad - Ahamad, Nur Syahidah (Faculty of Business and Management, 2008)
This research explores the effectiveness of promotional strategy implemented by Zoo Melaka. The dependent variable for this research is promotional strategy and the independent variables consist of advertising, sales promotion, personal selling and publicity. The research is conducted at Zoo Melaka where 50 questionnaires have been distributed. The questionnaires were distributed during the operational hours of zoo. According to the research, the researcher found that the most acceptable promotional tool by visitors is television. Furthermore, in order to attract and encourage more visitors, Zoo Melaka should make aggressive promotion and offer more benefit for their member's dub. Other than that, all staffs should have enough and deep knowledge regarding Zoo Melaka and also should make aggressive publicity for Zoo Melaka. Through the findings of the research, it can be concluded that all of the four components of promotional strategy implemented by Zoo Melaka is effective.